“Like a fragment of the old world”: The Historical Regression of Quebec City in Travel Narratives and Tourist Guidebooks, 1776–1913 - Little, Jack (Urban History Review / Revue d'histoire urbaine, 2012)
Although it was largely ignored in the late eighteenth century, Quebec City figured prominently on the North American circuit of British travel writers in the earlier years of the nineteenth century, when the obligatory description of the view from and of Cape Diamond served as a metaphor for imperial expansion. From this perspective, Quebec was not only the site where Wolfe had won his great battle against the French in 1759, it was also a military stronghold and gateway to an empire that stretched to the Pacific Ocean. The story told by American travel narratives and tourist guidebooks was rather different. They tended to see Quebec as unprogressive and of interest primarily because of its antiquity—an image that local tourism promoters turned to the city’s advantage as its population growth stalled in the later nineteenth century. With the arrival of the railways and the growing reliance on tourism as an industry, Quebec City’s image reverted to an early stage of the historical progress narrative, becoming frozen in a mythical past as a picturesque fragment of medieval Europe.